1994
DOI: 10.1123/ijsn.4.3.265
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Indices of Hydration Status

Abstract: Athletes and researchers could benefit from a simple and universally accepted technique to determine whether humans are well-hydrated, euhydrated, or hypohydrated. Two laboratory studies (A, B) and one field study (C) were conducted to determine if urine color () indicates hydration status accurately and to clarify the interchangeability of , urine osmolality (), and urine specific gravity () in research. , , and were not significantly correlated with plasma osmolality, plasma sodium, or hemato-crit. This sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
487
3
34

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 609 publications
(556 citation statements)
references
References 0 publications
16
487
3
34
Order By: Relevance
“…Participants were required to consume 1 liter of water on the night prior to testing and 0.5 liter on the day of visit 6. Adequate hydration (urine specific gravity Յ1.020) was confirmed prior to venous catherization via urine refractometry (2). Before the acute exercise protocol, an intravenous catheter was inserted into the antecubital vein.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were required to consume 1 liter of water on the night prior to testing and 0.5 liter on the day of visit 6. Adequate hydration (urine specific gravity Յ1.020) was confirmed prior to venous catherization via urine refractometry (2). Before the acute exercise protocol, an intravenous catheter was inserted into the antecubital vein.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments by Armstrong et al [22] showed urine colour can be used to assess hydration status. By scaling urine colour against a numbered scale, the authors demonstrated a crude assessment of hydration for situations where exactness is not essentially required.…”
Section: Urine Color and Urine Specific Gravitymentioning
confidence: 99%
“…An investigation by Francesconi et al [34] showed that participants who lost up to 3% of body mass through sweating did not show any difference in haematocrit or serum osmolality immediately after. Armstrong et al [22] and Sherrif [14] suggested that the volume of blood plasma does not necessarily change until a certain amount of water had been lost in order to maintain cardiovascular stability. Also, if water losses are accompanied by loss of salt or other nutrients, haemoconcentration may not be a reliable indicator of hydration status.…”
Section: Analysis Of Blood Samplementioning
confidence: 99%
“…However, to date, there has been no universally accepted biomarker that reflects an increase in hydration status in response to an increase in beverage intake. Therefore, no markers are defined as gold standard (4,6).…”
Section: Introductionmentioning
confidence: 99%